The Microbiological Profile of Community-Acquired Pneumonia in Pediatric Patients in Brazil - , Guilherme Vieira Lima, Rafael Rodrigues Leite, Sandriny Maria de Almeida Oliveira, Sara Maria Bié Gomes, Sávio Benvindo Ferreira (Archives of Current Research International, 2023)
Aims: Identifying the main pathogens causing Community Acquired Pneumonia in the pediatric population. Study Design: It is a narrative review, a qualitative study. Place and Duration of Study: Multidisciplinary Laboratory of Scientific Design and Writing (LaMDEC), Julio Bandeira University Hospital (HUJB), Cajazeiras, Paraíba, Brazil, from May 2023 to June 2023. Methodology: A narrative literature review method was adopted, with research carried out in the following databases: Google Scholar, Scientific Scientific Electronic Library Online (SciELO), PubMed, LILACS and Virtual Health Library (BVS). Results: A relevant prevalence of the bacterial pathogens Streptococcus pneumoniae, Mycoplasma pneumoniae and Staphylococcus aureus, and the viral etiological agent Respiratory Syncytial Virus, depending on the age of the affected patients, was observed in the literature in the pediatric population. Conclusion: A relevant prevalence of the bacterial pathogens Streptococcus pneumoniae, Mycoplasma pneumoniae and Staphylococcus aureus, and the viral etiological agent Respiratory Syncytial Virus, depending on the age of the affected patients, was observed in the literature in the pediatric population. However, the means used to confirm the etiology are still lacking in their methodological reliability, a fact that makes it important for the scientific community to develop and adopt more effective methods for the microbiological determination of the causes of pneumonia.